A quantum dot reflective film and preparation method thereof

By modifying the quantum dots and combining them with silicone resin, the problems of the stability and life cycle of existing quantum dot reflective films are solved, achieving higher reflective performance and stability.

CN119217759BActive Publication Date: 2025-04-01NINGBO CHANGYANG TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411723024.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-01
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The surface layer of the existing quantum dot reflective film is prone to wear and gas is prone to leak, making it difficult to guarantee the stability and life cycle of the quantum dots.

Method used

By modifying the quantum dots with PEG and combining them with maleic anhydride grafted silicone resin, quantum dot functional masterbatch is formed, and then mixed with polyester resin and additives, extruded and stretched to make a reflective film. The thickness of the intermediate film accounts for 80-92% of the total thickness.

Benefits of technology

The surface defects of quantum dots are improved, their luminous efficiency and light and chemical stability are improved, the reflective performance of the reflective film is enhanced, and the stability and life cycle of the quantum dots are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119217759B_ABST
    Figure CN119217759B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of reflective films, and provides a quantum dot reflective film and a preparation method thereof. The preparation method comprises the steps of: modifying quantum dots with PEG to obtain modified quantum dots, the PEG terminal contains amino groups, and the mass ratio of quantum dots to PEG is 1:50-100; grafting silicone resin with maleic anhydride to obtain maleic anhydride grafted silicone resin, the silicone resin is a vinyl silicone resin, and the viscosity is 60000-80000 cP; mixing the modified quantum dots and the maleic anhydride grafted silicone resin, and melt granulating to obtain quantum dot functional masterbatch; mixing the quantum dot functional masterbatch with polyester resin and auxiliary agent, extruding, stretching and forming a film as an intermediate film; the intermediate film and the outer films on both sides are combined into a reflective film, and the thickness of the intermediate film accounts for 80-92% of the total thickness. Modifying and grafting quantum dots improves the stability of quantum dots in the reflective film, and at the same time improves the reflective performance of the film. The present invention also provides a quantum dot reflective film obtained by the preparation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of reflective films, and in particular to a quantum dot reflective film and a preparation method thereof. Background Art

[0002] Quantum dot reflective film generally adds quantum dots directly into the coating or film layer to increase the brightness and color saturation of the reflected light, and uses a surface coating or an inert gas to protect the quantum dots from water and oxygen. For example, patent CN117930545A discloses a quantum dot reflective film and its preparation method, and a backlight module. The quantum dot reflective film includes: a resin layer, wherein the resin layer includes a plurality of embedded quantum dots and bubbles encapsulating the quantum dots, and the gas in the bubbles includes: an inert gas; a functional coating, which is arranged on the surface of the light-emitting side of the resin layer. This application solves or at least partially solves the technical problem of poor stability of the quantum dot film. However, there are still problems such as easy wear of the surface layer and easy leakage of gas, which makes it difficult to ensure the stability and life cycle of the quantum dots. Therefore, an ideal solution is needed. Summary of the invention

[0003] The invention provides a quantum dot reflective film and a preparation method thereof. The quantum dots are modified with PEG and grafted with an organic silicon resin. The dosage, viscosity and other parameters are limited to improve the stability of the quantum dots in the reflective film and improve the reflective performance of the film.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] A method for preparing a quantum dot reflective film comprises the following steps:

[0006] A. Modified quantum dots are obtained by modifying quantum dots with PEG, wherein the end of PEG contains an amino group, and the mass ratio of quantum dots to PEG is 1:50-100;

[0007] B. grafting maleic anhydride with silicone resin to obtain maleic anhydride grafted silicone resin, wherein the silicone resin is a vinyl silicone resin having a viscosity of 60000-80000 cP;

[0008] C. The modified quantum dots and the maleic anhydride grafted silicone resin are mixed in a mass ratio of 1-5:95-99, and melt granulated to obtain a quantum dot functional masterbatch;

[0009] D. Quantum dot functional masterbatch is mixed with polyester resin and additives, extruded and stretched to form a film as an intermediate film; the intermediate film is combined with the outer films on both sides to form a reflective film, and the thickness of the intermediate film accounts for 80-92% of the total thickness.

[0010] Preferably, the step of modifying quantum dots with PEG is: dispersing the quantum dots in methanol, adding PEG, reacting at 50-70° C. for 1-3 h, washing with methanol and drying to obtain modified quantum dots.

[0011] Preferably, the quantum dots are selected from one or more of CsPbBr3, CsPbI3, CdSe, CdSe / ZnS, InP / ZnS, PbSe / PbS, CdSe / CdS, CdTe / CdS and CdTe / ZnS; the quantum dots are in powder form; and the molecular weight of PEG is 2000-4000.

[0012] Preferably, the step of grafting the silicone resin with maleic anhydride is: mixing the silicone resin with maleic anhydride and a peroxide initiator, and extruding the mixture through an extruder to obtain the silicone resin grafted with maleic anhydride.

[0013] Preferably, the mass ratio of the silicone resin to maleic anhydride is 80-85:15-20.

[0014] Preferably, the peroxide initiator is dicumyl peroxide DCP or benzoyl peroxide BPO, and the amount used is 0.5-2% of the mass of the reaction system.

[0015] Preferably, the extrusion temperature is 165-200°C.

[0016] Preferably, the temperature of the melt granulation is 165-200° C., and the screw shearing speed is 100-150 rpm.

[0017] Preferably, the quantum dot functional masterbatch is mixed with the polyester resin and additives at a weight ratio of 10-30%.

[0018] Preferably, the additives of the intermediate film include titanium dioxide masterbatch, chain extender, nucleating agent and dispersant; the mass proportion of polyester resin in the intermediate film is 50-70%, and the mass proportion of titanium dioxide masterbatch is 15-20%.

[0019] Preferably, the raw material of the outer film includes 80-98% polyester resin and 2-20% auxiliary agent. As a further preferred auxiliary agent, an antioxidant and a water-blocking agent are included.

[0020] Preferably, the intermediate film raw material and the outer film raw material are respectively co-cast and extruded at the die head of the extruder through the melt flow channel in the form of a main layer and an auxiliary layer, and the cast sheet is cooled, stretched, and heat-set to obtain a reflective film; the stretching includes longitudinal and transverse stretching, and the transverse and longitudinal stretching ratios are each independently 2.5-3.2.

[0021] The invention also provides a quantum dot reflective film prepared by the preparation method.

[0022] Preferably, the thickness of the film is 100-300 μm.

[0023] Therefore, the beneficial effects of the present invention are as follows: (1) PEG can improve the surface defects of quantum dots. The defects of quantum dots are in an unstable state and will spontaneously form chemical bonds with the hydroxyl groups in the PEG molecular chain, so that the surface of the quantum dots can be passivated, thereby improving the luminous efficiency and light and chemical stability of the quantum dots. The PEG containing amino groups at the end makes the quantum dots carry amino groups, providing reactive groups for subsequent reactions. (2) During the double-drawing process, the silicone resin containing quantum dots will gradually separate and form pores with a size of 1 to 5 μm due to its incompatibility with the polyester resin. These pores play a role in blocking light, refraction and reflection in the reflective film. The size and shape of the pores of the reflective film determine the key performance of the reflectivity of the reflective film. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the structure of the quantum dot reflective film.

[0025] In the figure, 1, intermediate film, 11, quantum dots, 12, silicone resin, 13, pores, 2, outer film, 21, antioxidant and water barrier agent. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further described below through specific embodiments.

[0027] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art. Unless otherwise specified, parts are by weight, temperatures are expressed in ° C or at ambient temperature, and pressures are atmospheric pressure or near atmospheric pressure. There are many variations and combinations of reaction conditions (such as component concentrations, desired solvents, solvent mixtures, temperatures, pressures, and other reaction ranges) and conditions that can be used to optimize the purity and yield of the product obtained by the method, and only reasonable routine experiments will be required to optimize such method conditions.

[0028] Example

[0029] A method for preparing a quantum dot reflective film comprises the following steps:

[0030] (1) Quantum dot modification

[0031] The quantum dots were dispersed in methanol, PEG was added, the mass ratio of quantum dots to PEG was 1:50-100, the reaction was carried out at 50-70 °C for 1-3 h, and the modified quantum dots were obtained after washing with methanol and drying.

[0032] The quantum dots are selected from one or more of CsPbBr3, CsPbI3, CdSe, CdSe / ZnS, InP / ZnS, PbSe / PbS, CdSe / CdS, CdTe / CdS and CdTe / ZnS; the quantum dots are in powder form; the PEG terminal contains an amino group, and the amino group content is 8-10%; the PEG molecular weight is 2000-4000.

[0033] PEG can improve the surface defects of quantum dots. The defects of quantum dots are in an unstable state and will spontaneously form chemical bonds with the hydroxyl groups in the PEG molecular chain, passivating the surface of the quantum dots and improving the luminous efficiency and light and chemical stability of the quantum dots. PEG with amino groups at the end can bring amino groups to the quantum dots, providing reactive groups for subsequent reactions.

[0034] (2) Silicone resin grafted with maleic anhydride

[0035] The silicone resin and maleic anhydride are mixed in a mass ratio of 80-85:15-20, a peroxide initiator is added, and the mixture is extruded at a high temperature of 165-200° C. in an extruder with a screw length-to-diameter ratio L / D greater than 50 to obtain a silicone resin grafted with maleic anhydride.

[0036] The silicone resin is a vinyl silicone resin with a viscosity of 60000-80000 cP (viscosity at 25°C). The peroxide initiator is dicumyl peroxide DCP or benzoyl peroxide BPO, and the amount used is 0.5-2% of the mass of the reaction system.

[0037] Silicone resins have extremely high resistance to water and water vapor and very low water absorption.

[0038] (3) Quantum dots and silicone resin granulation

[0039] The modified quantum dots and the silicone resin grafted with maleic anhydride are uniformly mixed in a mass ratio of (1-5):(95-99), and melt granulation is performed at a temperature of 165-200°C and a screw shearing speed of 100-150 rpm to obtain a quantum dot functional masterbatch.

[0040] Under the action of high temperature and screw shearing, the anhydride group of maleic anhydride can undergo a generalized dehydration reaction with the amino group of the quantum dots and form a chemical bond, thereby chemically coupling to obtain a quantum dot functional masterbatch coupled with an incompatible resin.

[0041] (4) Extrusion casting

[0042] The reflective film has an ABA three-layer structure, the thickness of the A layer accounts for 4-10% of the total thickness, and the thickness of the B layer accounts for 80-92% of the total thickness. The thickness of the reflective film is 100-300 μm.

[0043] The raw material formula of layer A is: 80-98wt% polyester resin + 2-20wt% auxiliary agent. The raw material of layer A is fed into a conical mixer and mixed evenly, and melt-extruded at 265-285 °C through the auxiliary extruder of the twin-screw extruder. Among them, the auxiliary agent is an antioxidant and a water-blocking agent. The antioxidant can be selected from one or more of phenolic antioxidants 1010, 1076 or phosphorus antioxidants 168. In the embodiment, phenolic antioxidant 1010 is selected. The water-blocking agent is wollastonite water-blocking agent.

[0044] The raw material formula of layer B is: 50-70wt% polyester resin + 10-30wt% quantum dot functional masterbatch + 15-20wt% titanium dioxide masterbatch + balance additives. The raw material of layer B is crystallized, dried and mixed at 140-160 ℃, and then fed into a conical mixer for uniform mixing. It is melt-extruded at 265-285 ℃ by the main extruder of a single-screw extruder. The raw materials of layer B and layer A are co-cast and extruded at the die head in the form of a main layer and an auxiliary layer through a melt flow channel, and the cast sheet is cooled. Among them, the additives are chain extenders, nucleating agents, and dispersants. The chain extender can be selected from one of ethylenediamine (DA), N,N-dihydroxy (diisopropyl) aniline (HPA) or trimethylolpropane. In the following examples, ethylenediamine is selected to improve the strength of the melt and the toughness of the film during processing. The nucleating agent can be talcum powder or calcium carbonate. In the following examples, talcum powder is selected. The dispersant is polyethylene wax (PEW).

[0045] (5) Stretch film

[0046] The casting sheet is sequentially subjected to longitudinal stretching, transverse stretching, heat setting and rolling to obtain a quantum dot reflective film. The longitudinal stretching ratio and the transverse stretching ratio are independently 2.5-3.2.

[0047] During the double-drawing process, the silicone resin containing quantum dots is incompatible with the polyester resin and will gradually separate to form bubbles with a size of 1 to 5 μm. These bubbles play a role in blocking, refracting and reflecting light in the reflective film. The size and shape of the bubble of the reflective film determine the key performance of the reflectivity of the reflective film.

[0048] The structure of the quantum dot reflective film is as follows: Figure 1 As shown, there are three layers, namely, the middle film 1 in the middle and the outer films 2 on both sides of the middle film. Antioxidants and water barrier agents 21 are uniformly dispersed in the outer film 2. Quantum dot functional masterbatch is uniformly dispersed in the middle film 1, and the quantum dot functional masterbatch is composed of quantum dots 11 coated with silicone resin 12, and the presence of silicone resin 12 forms pores 13 during the stretching process.

[0049] In the quantum dot reflective film prepared by the present invention, the quantum dots are passivated by PEG, coupled with a hydrophobic organic silicone resin, and protected by a three-layer ABA resin layer to block water and oxygen, and have good stability and life cycle.

[0050] Example 1

[0051] A method for preparing a quantum dot reflective film, the steps are as follows:

[0052] (1) Quantum dot modification

[0053] CsPbBr3 quantum dot powder was dispersed in methanol, and PEG2000 containing terminal amino groups was added. The mass ratio of quantum dots to PEG was 1:80. The mixture was reacted at 60 °C for 2 h, washed with methanol and dried to obtain modified quantum dots.

[0054] (2) Silicone resin grafted with maleic anhydride

[0055] Vinyl silicone resin RH-S11H (viscosity 63000-73000 cP at 25 ℃) and maleic anhydride were mixed in a mass ratio of 82:18, 1wt% peroxide initiator DCP was added, and the mixture was extruded at 180 ℃ in an extruder with a screw length-to-diameter ratio L / D greater than 50 to obtain a maleic anhydride grafted silicone resin.

[0056] (3) Quantum dots and silicone resin granulation

[0057] The modified quantum dots and the silicone resin grafted with maleic anhydride were uniformly mixed in a mass ratio of 5:95, and melt granulated at 180°C and a screw shear speed of 120 rpm to obtain quantum dot functional masterbatch.

[0058] (4) Extrusion casting

[0059] The reflective film has an ABA three-layer structure, the thickness of the A layer accounts for 7% of the total thickness, and the thickness of the B layer accounts for 86% of the total thickness. The thickness of the reflective film is 200 μm.

[0060] The raw material formula of layer A is: 90wt% polyester resin + 10wt% additives (antioxidant and water barrier agent). The raw materials of layer A are fed into a conical mixer and mixed evenly, and then melted and extruded at 270°C through the auxiliary extruder of the twin-screw extruder.

[0061] The raw material formula of layer B is: 62wt% polyester resin + 20wt% quantum dot functional masterbatch + 15wt% titanium dioxide masterbatch + 2wt% chain extender + 0.5wt% nucleating agent + 0.5wt% dispersant. The raw material of layer B is crystallized and dried at 150℃, mixed, and then fed into a conical mixer for uniform mixing. It is melt-extruded at 270℃ through the main extruder of a single-screw extruder. The raw materials of layer B and layer A are co-cast and extruded at the die head in the form of a main layer and an auxiliary layer through a melt flow channel, and the cast sheet is cooled.

[0062] (5) Stretch film

[0063] The casting sheet is sequentially subjected to longitudinal stretching, transverse stretching, heat setting, and winding to obtain a quantum dot reflective film, wherein the longitudinal stretching ratio and the transverse stretching ratio are both 3.0.

[0064] Example 2

[0065] The difference from Example 1 is that the quantum dots are CdSe.

[0066] Example 3

[0067] The difference from Example 1 is that the quantum dots are InP / ZnS.

[0068] Example 4

[0069] A method for preparing a quantum dot reflective film, the steps are as follows:

[0070] (1) Quantum dot modification

[0071] CsPbBr3 quantum dot powder was dispersed in methanol, and PEG4000 containing an amino group at the end was added. The mass ratio of quantum dots to PEG was 1:50. The mixture was reacted at 50 °C for 3 h, washed with methanol and dried to obtain modified quantum dots.

[0072] (2) Silicone resin grafted with maleic anhydride

[0073] Vinyl silicone resin RH-S11H and maleic anhydride were mixed in a mass ratio of 85:15, 0.5wt% peroxide initiator DCP was added, and the mixture was extruded at 165°C in an extruder with a screw length-to-diameter ratio L / D greater than 50 to obtain a maleic anhydride grafted silicone resin.

[0074] (3) Quantum dots and silicone resin granulation

[0075] The modified quantum dots and the silicone resin grafted with maleic anhydride were uniformly mixed in a mass ratio of 1:99, and melt granulated at 165°C and a screw shear speed of 150 rpm to obtain quantum dot functional masterbatch.

[0076] (4) Extrusion casting

[0077] The reflective film has an ABA three-layer structure, the thickness of the A layer accounts for 7% of the total thickness, and the thickness of the B layer accounts for 86% of the total thickness. The thickness of the reflective film is 200 μm.

[0078] The raw material formula of layer A is: 80wt% polyester resin + 20wt% additives (antioxidant and water barrier agent). The raw materials of layer A are fed into a conical mixer and mixed evenly, and then melted and extruded at 265°C through the auxiliary extruder of the twin-screw extruder.

[0079] The raw material formula of layer B is: 50wt% polyester resin + 30wt% quantum dot functional masterbatch + 17wt% titanium dioxide masterbatch + 2wt% chain extender + 0.5wt% nucleating agent + 0.5wt% dispersant. The raw material of layer B is crystallized and dried at 140℃, mixed, and then fed into a conical mixer for uniform mixing. It is melt-extruded at 265℃ through the main extruder of a single-screw extruder. The raw materials of layer B and layer A are co-cast and extruded at the die head in the form of a main layer and an auxiliary layer through a melt flow channel, and the cast sheet is cooled.

[0080] (5) Stretch film

[0081] The casting sheet is sequentially subjected to longitudinal stretching, transverse stretching, heat setting, and winding to obtain a quantum dot reflective film, wherein the longitudinal stretching ratio and the transverse stretching ratio are both 2.5.

[0082] Example 5

[0083] A method for preparing a quantum dot reflective film, the steps are as follows:

[0084] (1) Quantum dot modification

[0085] CsPbBr3 quantum dot powder was dispersed in methanol, and PEG3000 containing terminal amino groups was added. The mass ratio of quantum dots to PEG was 1:100. The mixture was reacted at 70 °C for 1 h, washed with methanol and dried to obtain modified quantum dots.

[0086] (2) Silicone resin grafted with maleic anhydride

[0087] Vinyl silicone resin RH-S11H and maleic anhydride were mixed in a mass ratio of 80:20, 2wt% peroxide initiator DCP was added, and the mixture was extruded at 200°C in an extruder with a screw length-to-diameter ratio L / D greater than 50 to obtain a maleic anhydride grafted silicone resin.

[0088] (3) Quantum dots and silicone resin granulation

[0089] The modified quantum dots and maleic anhydride grafted silicone resin were uniformly mixed in a mass ratio of 3:97, and melt granulated at 200°C and a screw shear speed of 100 rpm to obtain quantum dot functional masterbatch.

[0090] (4) Extrusion casting

[0091] The reflective film has an ABA three-layer structure, the thickness of the A layer accounts for 7% of the total thickness, and the thickness of the B layer accounts for 86% of the total thickness. The thickness of the reflective film is 200 μm.

[0092] The raw material formula of layer A is: 98wt% polyester resin + 2wt% additives (antioxidant and water barrier agent). The raw materials of layer A are fed into a conical mixer and mixed evenly, and then melted and extruded at 285°C through the auxiliary extruder of the twin-screw extruder.

[0093] The raw material formula of layer B is: 70wt% polyester resin + 10wt% quantum dot functional masterbatch + 17wt% titanium dioxide masterbatch + 2wt% chain extender + 0.5wt% nucleating agent + 0.5wt% dispersant. The raw material of layer B is crystallized and dried at 160℃, mixed, and then fed into a conical mixer for uniform mixing. It is melt-extruded at 285℃ by the main extruder of a single-screw extruder. The raw materials of layer B and layer A are co-cast and extruded at the die head in the form of a main layer and an auxiliary layer through a melt flow channel, and the cast sheet is cooled.

[0094] (5) Stretch film

[0095] The casting sheet is sequentially subjected to longitudinal stretching, transverse stretching, heat setting, and winding to obtain a quantum dot reflective film, wherein the longitudinal stretching ratio and the transverse stretching ratio are both 3.2.

[0096] Comparative Example

[0097] Comparative Example 1

[0098] The difference from Example 1 is that the quantum dots are not modified with PEG.

[0099] Comparative Example 2

[0100] The difference from Example 1 is that in step (1), the mass ratio of quantum dots to PEG is 1:120, and the amount of PEG exceeds the preferred range.

[0101] Comparative Example 3

[0102] The difference from Example 1 is that the modified quantum dots are directly mixed to form a film, and are not melt-granulated with maleic anhydride grafted silicone resin to obtain quantum dot functional masterbatch.

[0103] Comparative Example 4

[0104] The difference from Example 1 is that in step (2), the viscosity of the silicone resin is lower than the preferred range.

[0105] Comparative Example 5

[0106] The difference from Example 1 is that in step (2), the viscosity of the silicone resin is higher than the preferred range.

[0107] Comparative Example 6

[0108] The difference from Example 1 is that in step (3), the mass ratio of modified quantum dots to maleic anhydride grafted silicone resin is 10:90, and the amount of maleic anhydride grafted silicone resin is lower than the preferred range.

[0109] Comparative Example 7

[0110] The difference from Example 1 is that the thickness of layer B accounts for 70% of the total thickness, which is lower than the preferred range.

[0111] Comparative Example 8

[0112] The difference from Example 1 is that the thickness of layer B accounts for 95% of the total thickness, which is higher than the preferred range.

[0113] Performance Testing

[0114] The performance of each embodiment and comparative example was tested using the following test method:

[0115] (1) Reflectivity: In accordance with GB / T3979-2008, the reflectivity was tested using a ColorQuest XE spectrophotometer (manufactured by Hunterlab) under D65 light source conditions using an integrating sphere d / 8° structure. The reflectivity data is the weighted average of the reflectivity at every 10 nm wavelength from 400 to 700 nm, and the weights correspond to the energy distribution curve of the D65 light source.

[0116] (2) Average brightness and brightness uniformity: Assemble the prepared sample into the backlight module, light up the backlight module, select the appropriate test mode, divide the light-emitting surface into 9 areas of 3×3, and use the Fusida BM-7A brightness meter for measurement. The measurement angle is 1°, and the distance between the brightness meter and the single-sided light-emitting surface of the backlight source is 50 cm. The brightness values ​​of 9 points on the light-emitting surface are measured. The tested brightness value is the brightness value of each point. Brightness uniformity = the lowest brightness value among 9 points / the highest brightness value among 9 points × 100%. Calculate and record this data.

[0117] (3) Tensile strength: According to GB / T 13542.4, cut a 15 mm wide and 220 mm long specimen. Place one end of the specimen into the clamp of the tensile machine, the machine is WD-5000E (computer-controlled electronic universal testing machine), keep the direction vertical, set the tensile speed to 100 mm / min after clamping, and record the tensile strength and elongation at break when the specimen breaks.

[0118] (4) Aging test: According to GB / T 2423.2-2008 standard, set the aging box temperature to 85 °C, place the initial sample after brightness measurement in the aging box, take it out after aging for 24 hours, and conduct brightness test.

[0119] The results are shown in Tables 1 and 2.

[0120] Table 1.

[0121]

[0122] Table 2.

[0123]

[0124] It can be seen from Table 1 and Table 2 that according to the results of Examples 1-3, different quantum dots (CsPbBr3, CdSe, InP / ZnS) grafted with incompatible resins (silicone resin) do not affect the reflectivity, but can improve the average brightness and brightness uniformity of the reflective film. Among them, CsPbBr3 has the most obvious improvement on the performance of the reflective film.

[0125] Compared with Example 1: (1) The quantum dots in Comparative Example 1 are not modified with PEG, and have many surface defects; and cannot be grafted onto incompatible resins (silicone resins) through PEG, which is equivalent to the quantum dots being dispersed throughout the interior of the reflective film, resulting in poor brightness uniformity and luminance performance. At the same time, the quantum dots on the surface will be exposed to water and oxygen, resulting in quenching, and the brightness decay and XY coordinate offset after aging are large. In Comparative Example 2, excessive PEG is used, which will lead to over-modification of quantum dots, reduced quantum dot performance, and reduced brightness enhancement effect.

[0126] (2) Comparative Example 3 was not mixed with the silicone resin for granulation, and no holes could be formed during stretching, so the reflectivity was seriously reduced. The viscosity of the silicone resin in Comparative Examples 4 and 5 was not within the preferred range, and the viscosity of the silicone resin would affect the film-forming property and refractive index. The lower the viscosity, the better the fluidity, and the film is likely to form a layered structure after cooling, which is easy to delaminate, affecting its stretching properties, and the decrease in porosity leads to a decrease in reflectivity; the higher the viscosity, the worse the fluidity, and it is easy to form local hardening, which will also affect the reflectivity and stretching properties.

[0127] (3) In Comparative Example 6, the absorption and emission spectra of the quantum dots partially overlap, resulting in the self-absorption effect being enhanced as the concentration of the quantum dots increases, leading to a decrease in the fluorescence intensity of the quantum dots, and thus reducing the brightness of the reflective film.

[0128] (4) In comparative example 7, the thickness of layer B accounts for 70%, resulting in a large loss of light passing through layer A, and the effect and brightness of reflected light will decrease. In comparative example 8, the thickness of layer B accounts for 95%, resulting in excessive porosity of layer B, reduced tensile strength of the reflective film, and easy film breakage.

[0129] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a quantum dot reflective film, characterized in that: The following steps are involved: A. Modified quantum dots are obtained by modifying quantum dots with PEG, wherein the end of PEG contains an amino group, and the mass ratio of quantum dots to PEG is 1:50-100; B. grafting maleic anhydride with silicone resin to obtain maleic anhydride grafted silicone resin, wherein the silicone resin is a vinyl silicone resin having a viscosity of 60000-80000 cP; C. The modified quantum dots and the maleic anhydride grafted silicone resin are mixed in a mass ratio of 1-5:95-99, and melt granulated to obtain the quantum dot functional masterbatch; D. Quantum dot functional masterbatch is mixed with polyester resin and additives at a weight ratio of 10-30%, extruded and stretched to form a film as an intermediate film; the intermediate film and the outer films on both sides are combined into a reflective film, and the thickness of the intermediate film accounts for 80-92% of the total thickness.

2. The method for preparing a quantum dot reflective film according to claim 1, characterized in that: The steps of PEG modification of quantum dots are as follows: dispersing the quantum dots in methanol, adding PEG, reacting at 50-70°C for 1-3 h, washing with methanol and drying to obtain modified quantum dots.

3. A method for preparing a quantum dot reflective film according to claim 1 or 2, characterized in that: The quantum dots are selected from one or more of CsPbBr3, CsPbI3, CdSe, CdSe / ZnS, InP / ZnS, PbSe / PbS, CdSe / CdS, CdTe / CdS and CdTe / ZnS; the quantum dots are in powder form.

4. The method for preparing a quantum dot reflective film according to claim 1, characterized in that: The steps of grafting the organic silicone resin with maleic anhydride are as follows: mixing the organic silicone resin with maleic anhydride and a peroxide initiator, and extruding the mixture through an extruder to obtain the organic silicone resin grafted with maleic anhydride.

5. The method for preparing a quantum dot reflective film according to claim 1, characterized in that: The additives of the intermediate film include titanium dioxide masterbatch, chain extender, nucleating agent and dispersant; the mass proportion of polyester resin in the intermediate film is 50-70%, and the mass proportion of titanium dioxide masterbatch is 15-20%.

6. The method for preparing a quantum dot reflective film according to claim 1 or 5, characterized in that: The raw materials of the outer film include 80-98% polyester resin and 2-20% additives.

7. The method for preparing a quantum dot reflective film according to claim 1, characterized in that: The intermediate film raw material and the outer film raw material are respectively co-cast and extruded in the form of a main layer and an auxiliary layer at the die head of the extruder through a melt flow channel, and the cast sheet is cooled, stretched, and heat-set to obtain a reflective film; the stretching includes longitudinal and transverse stretching, and the transverse and longitudinal stretching ratios are independently 2.5-3.

2.

8. A quantum dot reflective film, characterized in that: Prepared by any preparation method of claims 1-7.

9. The quantum dot reflective film according to claim 8, characterized in that: The thickness of the membrane is 100-300 μm.

Citation Information

Patent Citations

  • White reflective polyester film and preparation method thereof

    CN104608446A

  • Semiconductor nanocrystal-based cellular imaging

    US20030113709A1

  • Nanocrystal-polydimethylsiloxane composite and preparation method thereof

    US20090281265A1